(untitled) (Journal of Asian Development Studies, 2024)
American Psychological Association (APA) has launched a new style known as the Seventh Edition. But then, Pakistani researchers and scholars often need to correct citing and referencing in APA style seventh edition. The present research divulges the most common issue which frequently detected in the academic writings of Pakistani ESL researchers and scholars. The mixed method is used in this research, and the population of the study was the scholarly writings of the English linguistics department students of a well-known private university. A sample size of thirty assignments was selected by using a random sampling technique. These assignments were used as an instrument for the purpose of assembling data. The congregated statistics were later analyzed by using the content analysis technique by reading these assignments; the same method was used by (Lodhi et al., 2019; Nuraini, 2019) to analyze data. The analyzed data was presented in tables and graphs in numerical form. The analyzed data was presented in figures and tables in numerical form. The findings of the research revealed that ESL students committed different types of errors in their academic writing. On the base of these research findings, the researchers constituted some recommendations for future researchers and scholars. This research will prove helpful for researchers and scholars in overcoming their errors in citations and references.